2017
DOI: 10.1111/cdev.12907
|View full text |Cite
|
Sign up to set email alerts
|

Judging a Book by Its Cover: Children's Facial Trustworthiness as Judged by Strangers Predicts Their Real‐World Trustworthiness and Peer Relationships

Abstract: This longitudinal research examined whether children's facial trustworthiness as judged by strangers can predict their real-world trustworthiness and peer acceptance. Adults (Study 1) and children (Study 2) judged the facial trustworthiness of 8- to 12-year-old children (N = 100) solely based on their photographs. The children's classmates were asked to report their real-world trustworthiness and peer acceptance. Children's facial trustworthiness reliably predicted these outcomes both initially when the photog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 53 publications
7
31
0
Order By: Relevance
“…There is also some evidence that adults can form accurate impressions of trustworthiness (Li, Heyman, Mei, & Lee, 2017) and honesty (Zebrowitz et al, 1996) from A KERNEL OF TRUTH IN IMPRESSIONS 6 children's faces. Adults' impressions of trustworthiness from children's faces predicted actual trustworthiness in those children one year later (Li, et al, 2017). This result suggests there may be valid signals of trustworthiness in children's faces, whether this link arises through a self-fulfilling prophecy or is based on evolution.…”
Section: Are Impressions Of Children's Faces Accurate?mentioning
confidence: 99%
See 3 more Smart Citations
“…There is also some evidence that adults can form accurate impressions of trustworthiness (Li, Heyman, Mei, & Lee, 2017) and honesty (Zebrowitz et al, 1996) from A KERNEL OF TRUTH IN IMPRESSIONS 6 children's faces. Adults' impressions of trustworthiness from children's faces predicted actual trustworthiness in those children one year later (Li, et al, 2017). This result suggests there may be valid signals of trustworthiness in children's faces, whether this link arises through a self-fulfilling prophecy or is based on evolution.…”
Section: Are Impressions Of Children's Faces Accurate?mentioning
confidence: 99%
“…It is possible that these ambient images capture more valid information about behaviour and personality than face images taken in the lab under controlled conditions, which the majority of accuracy studies have used (cf. Alaei & Rule, 2019;Foo et al, 2019;Li et al, 2017;Penton-Voak et al, 2006;Pound, Penton-Voak, & Brown, 2007;Pound et al, 2008;Rhodes et al, 2013;Stirrat & Perrett, 2010;Sutherland et al, 2018). For example, nicer children might be more likely to smile for their parent's photograph, or more likely to be naturally captured smiling, than children who are less nice.…”
Section: Why Might Impressions Of Niceness Be Accurate?mentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed that, based on thin slice video fragments, youth's externalizing problems and temperament can be judged above chance levels by unacquainted observers (Tackett et al, 2017). Another study using photographs showed that children's trustworthiness can be judged above chance levels by unacquainted adults and children as well (Li et al, 2019). Judgments of the children's trustworthiness were mediated by the extent to which the children were well-liked among their classroom peers.…”
mentioning
confidence: 99%